Huangqin Decoction Exerts Beneficial Effects on Rotenone-Induced Rat Model of Parkinson's Disease by Improving Mitochondrial Dysfunction and Alleviating Metabolic Abnormality of Mitochondria - Gao, Li; Cao, Min; Du, Guan-hua; Qin, Xue-mei (Frontiers in Aging Neuroscience, 2022)
Parkinson's disease (PD) is a common neurodegenerative disease, and the pathogenesis of PD is closely related to mitochondrial dysfunction. Previous studies have indicated that the single Chinese herbs of Huangqin Decoction (HQD), including Scutellariae Radix, licorice, Paeoniae Radix Alba, have therapeutic effects on PD, but whether HQD has therapeutic effect on PD has not been reported. In this work, the protective effects of HQD on rotenone-induced PD rats were evaluated by behavioral assays (open field, rotating rod, suspension, gait, inclined plate, grid) and immunohistochemistry. The mechanisms of HQD on attenuation of mitochondrial dysfunction were detected by biochemical assays and mitochondrial metabolomics. The results showed that HQD (20g/kg) can protect PD rats by improving motor coordination and muscle strength, and increasing the number of TH positive neurons in PD rats. Besides, HQD can improve mitochondrial dysfunction by increasing the content of mitochondrial complex I and ATP. Mitochondrial metabolomics analysis revealed that the ketone body of AcAc in rotenone group was significantly higher than that of the control group. Ketone bodies have been known to be used as an alternative energy source to provide energy to the brain when glucose was deficient. Further studies demonstrated that HQD could increase the expression of glucose transporter GLUT1, the content of tricarboxylic acid cycle rate-limiting enzyme CS and the level of HK in PD rats, but decrease the content of ketone bodies (AcAc and β-HB) and the expression of their transporters (MCT1). Our study revealed that the decrease of glucose metabolism in rotenone group was parallel to the increase of substitute substrates (ketone bodies) and related transporters, and HQD could improve PD symptoms by activating aerobic glycolysis pathway.